Do gender and age of bank clients have an impact on bank card usage? - Ajtene Avdullahi; Vjosa Fejza Ademi (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
This paper attempts to investigate the ownership and usability of debit and credit cards in Kosovo focusing on two demographic variables: the gender and age of the bank's clients. For research purposes, the Central Bank of Kosovo (CBK) data are used for two consecutive years: 2015 and 2016. The comparative method is used to compare the clients’ behavior on the choice of the method to conduct payment and the usage of credit and debit cards in Kosovo banks for two consecutive years 2015 and 2016 based on the gender and age of bank clients. The results show that there is a gender gap, as debit and credit cards are owned and used more by males than females in all age groups and payment types. Whereas, for the variable age, the results show that both debit and credit cards are mostly used by customers aged 25-35 years followed by those 18-25 years. Based on the results of the paper, conclusions were drawn and some suggestions were given. We suggest that banks should do more to enhance the ownership and usage of debit and credit cards by females and elderly clients. Regarding the variable gender, we suggest that banks should offer credit and bonus cards with preferential rates to female entrepreneurs considering the very small number of female entrepreneurs to boost female entrepreneurship and decrease female unemployment in Kosovo.